Estimation of Several Commercial, Phenotypic and Reproductive Traits' Performance, Using the Quantitative Genetic Method for Kamper Chicken Line - I Wayan Swarautama Mahardhika; Abiyyayumna Rif’at Chasnaurosyiqoh; Joseph Chohansandhika; Feren Putri Sholiha; Nurachmad Bagas Indriarto; Budi Setiadi Daryono (Biogenesis: Jurnal Ilmiah Biologi, 2020)
In this study the genetic resource of Pelung chicken from Cianjur, West Java, Indonesia, was exploited. Pelung chicken has a higher body weight growth, unique meat flavor, and superior posture, compared with other indigenous breeds. Kamper chicken line selective breeding program was conducted, to increase the performance of Pelung breed by crossing with Layer Lohmann Brown-Classic. The Layer Lohmann Brown-Classic is an imported laying-type breed, which is widely known for its reproductive performance, based on the egg productivity. This study aims to use quantitative genetic method in estimating the commercial and reproductive traits' performance of Kamper chicken line. Based on commercial, phenotypic and reproductive traits, the progenies in Kamper chicken line have significant improvements, compared to the parental cross of Pelung and Layer Lohmann Brown-Classic. The quantitative genetic method was used in describing and underlying some phenomenon, in the selective breeding program. The results showed that the phenotypic and reproductive types of progenies in Kamper chicken, have significant improvements compared to the parental crossing of Pelung breed and Layer Lohmann Brown-Classic. Although quantitative genetic method is utilized in basic breeding program with significant precision and rapidness, it is only used in the preliminary study, for the advanced type. Therefore, the addition of quantitative trait loci (QTL), provide a more thorough genetic examination, and play a role in selective breeding program.